KEKUATAN PEMBUKTIAN SURAT SEBAGAI ALAT BUKTI DALAM PERKARA PERDATA - Lubis, Fauziah; Harahap, Nanda Asri Aulia; Putri, Amy Amalia; Nugraha, M. Akbar; Ritonga, M. Arif Ramadhan; Rangkuty, Kayla Salsabila (Gapenas Publisher, 2025)
Legal Evidence is an important part that determines the process of proving civil cases. Among the various means of proof recognized in civil procedural law, written documents are often used as primary evidence because of their real nature and can be verified through records or archives. This study focuses on the analysis of evidentiary data from letters as evidence, covering authentic deeds and private deeds, and their use in court practice. The method used is normative juridical, with an approach to relevant laws and regulations, legal doctrine, and court decisions. The research findings indicate that written documents, especially authentic deeds, have strong evidentiary value because they fulfill the elements of formality and legal substance, so they can be a strong basis for judges in making decisions. Meanwhile, deeds that are not made before authorized officials have weaker evidentiary power and usually require strengthening through recognition or additional evidence. Overall, the level of success in the process of proving civil cases is highly dependent on the validity and legal force of the written documents submitted..